3.- EFL IN-SERVICE TEACHERS’ SELF-REPORTED PERSPECTIVES ON ENGLISH LANGUAGE ASSESSMENT - Díaz Larenas, Claudio; Tagle Ochoa, Tania; Ortiz Navarrete, Mabel; Gómez Paniagua, Juan Fernando (Nueva Revista del Pacífico, 2022)
Abstract:The purpose of the following quantitative non-experimental and cross-sectional research study is to examine in-service teachers’ perceived views, skills, and practices towards the assessment of the English language. A sample of 315 in-service Chilean teachers took part in this study and data was collected through the Classroom Assessment Practices and Skills (CAPS) scale. Descriptive statistics and exploratory factor analysis were used to analyze the results. Findings indicated that in-service teachers perceived monitoring students´ learning as the purpose of assessment and agreed on the importance of diagnostic exams. Participants also considered making sure tests included all content taught and the use of assessment results for planning, as strong skills. Finally, the in-service teachers´ most frequent practices were associated with the design and feedback of assessment instruments.Resumen:El siguiente estudio de investigación cuantitativa no experimental y transversal busca examinar las opiniones, habilidades y prácticas percibidas de profesores respecto a la evaluación del idioma inglés. Participaron 315 profesores chilenos, cuyos datos se recogieron usando la escala Classroom Assessment Practices and Skills (CAPS). Se utilizó estadística descriptiva y análisis factorial exploratorio para el análisis de datos. Los resultados indicaron que los profesores percibían el monitoreo del aprendizaje como el propósito de la evaluación y estaban de acuerdo en la importancia de la evaluación diagnóstica. Los participantes también consideraron como fortalezas el asegurarse de que los exámenes incluyeran todo el contenido enseñado y el uso de los resultados de la evaluación para planificación. Por último, las prácticas más frecuentes de los profesores estaban asociadas al diseño y la retroalimentación de los instrumentos de evaluación.